Electron paramagnetic resonance of erbium doped silicon - DONEGAN, JOHN FRANCIS; BARKLIE, ROBERT CHARLES (American Institute of Physcis, 1996)
Electron paramagnetic resonance measurements have been made on samples of float zone silicon, implanted with 1015 Er/cm2. One sample was coimplanted with oxygen to give an impurity concentration of 1020 O/cm3 and 1019 Er/cm3. In this coimplanted sample, sharp lines are observed which are identified as arising from a single spin 1/2 Er31 center having a g tensor exhibiting monoclinic C1h symmetry. The principal g values and tilt angle are g150.80, g255.45, g3512.60, and t52.6?. In the absence of O, the sharp lines are not observed. No Er31 cubic centers were detected in either sample. Possible structures for the center are discussed.
PUBLISHED
Keywords: SILICON; DOPED MATERIALS; ERBIUM ADDITIONS; ION IMPLANTATION